Mark Norval : Kimberley artist - his story and work - Norval, Mark.; Schiel, Marty (West Footscray, Vic. : Moonrise Media, 1999)
Life story and art of Mark Norval - autobiography; career as an art teacher in Derby ; portraits and landscapes illustrating concern for the Kimberley and and its people ; Mowanjum Wandjina artists and Mowanjum community.
Keywords: Norval, Mark; Art, Australian -- Western Australia -- Kimberley; Aboriginal Australians -- Western Australia -- Kimberley; Ngarinyin / Ungarinyin people (K18) (WA SE52-01); Art - Subjects - Wandjina; Art - Artists - Men; History - Biographies - Indigenous - Autobiographies; Worrorra people (K17) (WA SD51-16); Art - Painting; Education - Teachers - Teacher education; Art - Painting - Acrylic; Wunambal people (K22) (WA SD51-12); Australia -- In art; Mowanjum (WA West Kimberley SE51-07); Kimberley area (WA SD51, SD52, SE51, SE52); Derby (WA West Kimberley SE51-07)